Dealing with global terrorism - Saighal, Vinod (New Delhi, 2003)
This book goes beyond the well-known by-lanes of the phenomenon and provides a tantalising glimpse of how the world is probably missing the wood for the trees in its fight against global terrorism. The author shows how national response patterns, ignoring several alternative strategies, still hover between retaliatory overkill. Delving into territory that has seldom been charted by scholars and experts writing on the subject, this book is particularly discernible in his views on: Breaking the Definitional Impasse that has eluded the comity of nations; looking beyond Iraq; countering suicide missions; and future projections to tackle the menace of global terrorism.
Keywords: Global terrorism: the way forward